Proceedings from the NICHD Conference on the Uterine Fibroid Research Update Workshop - Catherino, William H. (2011)
The purpose of the National Institutes of Health conference Fibroid Research Workshop in September 2007 was to bring Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) funded fibroid investigators together to discuss basic science and clinical research advances on uterine leiomyomata. General topics included advances in epidemiology, etiology, therapeutic approaches, and clinical trial challenges; suggestions for advancement basic understanding, clinical intervention, clinical trials, and future directions were highlighted.